I.L. Caragiale. Despre autor, cititor și diferite mecanisme de seducere, pornind de la O conferență : I.L. Caragiale. On the author, the reader, and the various mechanisms of seduction, starting from A lecture - Diaconu, Mircea A. (Swedish Journal of Romanian Studies, 2024)
The present text aims to problematise the work of I.L. Caragiale through the lens of reception theories, hermeneutics, and textuality while at the same time questioning some of the structuring themes of his writing, such as truth, the quest and the reader. Using texts such as ‘O conferență’, ‘Două loturi’, ‘Inspecțiune’, ‘Năpasta’, ‘D’ale carnavalului’, ‘Abu Hassan’, ‘1 Aprilie’ and others, the author aims to highlight elements of substance, attitude and style that converge in Caragiale’s writing, which, beyond the social, it associates the metaphysical comic or the idea of empty transcendence with the concern for truth, meta-textuality or the social. In this context, the proximity of I.L. Caragiale to Alphonse Allais or Henry James, in the interpretations of Umberto Eco and Wolfgang Iser, is supported beyond the similarities that legitimise the reading of I.L. Caragiale from the perspective of reception theories, by the fact that their relevant texts were written at the height of the Belle Époque. Therefore, Caragiale’s world appears as a luminous, complicit, seductive irony.